Business English Literacy in Improving the Effectiveness of MSME Businesses - Thamrin, Nani; Solihat, Dadang; Agustiana, Vina (International Journal Administration, Business & Organization, 2024)
This study examines the impact of Business English literacy on the effectiveness of Micro, Small, and Medium Enterprises (MSMEs). This study employs a qualitative research design to investigate the impact of Business English literacy on the effectiveness of Micro, Small, and Medium Enterprises. In today's globalized business environment, proficiency in Business English is crucial for MSMEs seeking to expand their market reach, engage in international trade, and enhance communication with global partners. The research explores how improved English literacy contributes to better business outcomes, such as increased sales, optimized marketing strategies, and more efficient operations. The study underscores the strong correlation between Business English skills and business success by analysing case studies and conducting surveys with MSME owners and employees. Investing in Business English training programs can significantly enhance the growth and competitiveness of MSMEs in the global market.